2019
DOI: 10.1164/rccm.201811-2087oc
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette Vapor with Nicotine Causes Airway Mucociliary Dysfunction Preferentially via TRPA1 Receptors

Abstract: of Health (NIH) -F32-HL140729 (to S.C.) and R01 HL139365 (to M.S.) RUNNING TITLE: Vaped nicotine impairs mucociliary function preferentially via TRPA1 SUBJECT CATEGORY DESCRIPTOR: 6.17 Smoking Health Effects TOTAL WORD COUNT: 3985 AT A GLANCE COMMENTARY: Scientific Knowledge on the Subject E-cigarettes are marketed as safer alternatives to conventional cigarettes due to their defined composition and noncombustible nature. However, it is unclear how exposure to e-cigarette vapor, colloquially referred to as "va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 56 publications
0
86
1
2
Order By: Relevance
“…Evidence from multiple groups including us reported the involvement of oxidative stress in CFTR dysfunction [53]. Thus, while our data specifically addresses the role of acrolein in CFTR dysfunction, these data do not exclude the role of other oxidative agents present in smoke [53] such as heavy metal toxins like cadmium [11], hypoxic injury [54] and nicotine [55,56]. In contrast, Savitsky and colleagues found that the particular matter in SHS was mostly responsible for CFTR dysfunction.…”
Section: Discussioncontrasting
confidence: 65%
“…Evidence from multiple groups including us reported the involvement of oxidative stress in CFTR dysfunction [53]. Thus, while our data specifically addresses the role of acrolein in CFTR dysfunction, these data do not exclude the role of other oxidative agents present in smoke [53] such as heavy metal toxins like cadmium [11], hypoxic injury [54] and nicotine [55,56]. In contrast, Savitsky and colleagues found that the particular matter in SHS was mostly responsible for CFTR dysfunction.…”
Section: Discussioncontrasting
confidence: 65%
“…6,47 These receptors induce airway surface liquid volume loss and decrease mucus density. 6,47 Other studies also reported that formaldehyde in ECIG-generated aerosols related to DNA strand breaks and cell death and propylene glycol thicken the respiratory epithelium by increasing the number of goblet cells and increasing the content of mucin within the goblet cell. 6,36 Strength and Limitation of the Study…”
Section: Xavier Et Al 2013 20mentioning
confidence: 99%
“…Still, a recent review of the evidence by National Academies of Sciences, Engineering and Medicine concluded that ECIG aerosol contains fewer numbers and lower levels of most toxicants than does smoke from combustible tobacco cigarettes [60], while a review by Public Health England stated that, compared with cigarettes, heated tobacco products are likely to expose users and bystanders to lower levels of particulate matter and harmful and potentially harmful compounds [61]. In vitro studies have also shown potentially adverse biological effects of these products [62,63].However, some clinical studies in smokers switching to ECIGs have reported improvement in physiologic parameters such as endothelial function [64] and respiratory function in asthmatics [65].Therefore, the global consensus is that a lot more research is needed to accurately quantify the harm reduction potential of these nicotine delivery products relative to tobacco cigarettes, as well as the effects of their use by non-smokers.…”
Section: Discussionmentioning
confidence: 99%